2016
DOI: 10.3390/sports4030042
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of New Zealand Blackcurrant Extract on Maximal Sprint Speed during the Loughborough Intermittent Shuttle Test

Abstract: New Zealand blackcurrant (NZBC) extract has been shown to enhance high-intensity intermittent treadmill running. We examined the effects of NZBC extract during the Loughborough Intermittent Shuttle Test (LIST) which involves 5 × 15 min blocks with intermittent 15-m maximal sprints, interspersed by moderate and high-intensity running to simulate team sport activity, and a subsequent run to exhaustion. Thirteen males (age: 22 ± 1 year, trueV˙O2max: 50 ± 5 mL·kg−1·min−1) participated in three indoor sessions (T: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 39 publications
4
39
1
Order By: Relevance
“…For example, Perkins et al (2015) observed an increase of 10.6% (P=0.023) in total running distance during an incremental intermittent high-intensity running protocol to exhaustion on a treadmill (placebo 3871±622 vs. blackcurrant 4282±833 m) and Murphy et al (2017) observed an increased performance of 0.82% (P=0.034) for a repeated 4 km cycling time-trial (placebo 771±60 vs. blackcurrant 764±56 s), but sample size could have been a limitation to allow firm conclusions for each of the two separate 4 km tests. Increased resistance to fatigue during exercise has also been shown following intake of blackcurrant extract with less slowing of maximal sprint running in the last 15-minute block of the Loughborough Intermittent Shuttle Test (Willems et al, 2016). The positive effects of blackcurrant extract on exercise performance have been identified in trained cyclists (Cook et al, 2015;Murphy et al, 2017;Willems et al, 2015), active but untrained males (Perkins et al, 2015;Willems et al, 2016) and trained youth footballers (Godwin et al, 2017).…”
Section: Exericse Performancementioning
confidence: 98%
See 3 more Smart Citations
“…For example, Perkins et al (2015) observed an increase of 10.6% (P=0.023) in total running distance during an incremental intermittent high-intensity running protocol to exhaustion on a treadmill (placebo 3871±622 vs. blackcurrant 4282±833 m) and Murphy et al (2017) observed an increased performance of 0.82% (P=0.034) for a repeated 4 km cycling time-trial (placebo 771±60 vs. blackcurrant 764±56 s), but sample size could have been a limitation to allow firm conclusions for each of the two separate 4 km tests. Increased resistance to fatigue during exercise has also been shown following intake of blackcurrant extract with less slowing of maximal sprint running in the last 15-minute block of the Loughborough Intermittent Shuttle Test (Willems et al, 2016). The positive effects of blackcurrant extract on exercise performance have been identified in trained cyclists (Cook et al, 2015;Murphy et al, 2017;Willems et al, 2015), active but untrained males (Perkins et al, 2015;Willems et al, 2016) and trained youth footballers (Godwin et al, 2017).…”
Section: Exericse Performancementioning
confidence: 98%
“…Increased resistance to fatigue during exercise has also been shown following intake of blackcurrant extract with less slowing of maximal sprint running in the last 15-minute block of the Loughborough Intermittent Shuttle Test (Willems et al, 2016). The positive effects of blackcurrant extract on exercise performance have been identified in trained cyclists (Cook et al, 2015;Murphy et al, 2017;Willems et al, 2015), active but untrained males (Perkins et al, 2015;Willems et al, 2016) and trained youth footballers (Godwin et al, 2017). The effects in elite athletes are unknown and need to be examined in future research, especially in those with a relatively low anthocyanin intake.…”
Section: Exericse Performancementioning
confidence: 98%
See 2 more Smart Citations
“…Performance improvements under various conditions. (Perkings et al, 2015; Willems et al, 2016) have demonstrated an ergogenic effect of NZBC extract after a seven-day intake phase. The aim of this study is to examine the in-fluence of NZBC extract on performance in the Yo-Yo Intermittent Recovery Test (Yo-YoIR1).…”
Section: Special Aspects Of Training and Testing In Hypoxia And Hyperoxiamentioning
confidence: 99%